2019
DOI: 10.20473/jr.v3-i.2.2017.47-51
|View full text |Cite
|
Sign up to set email alerts
|

Aspirasi Jarum Pentul yang Tertanam 10 Hari di Bronkus Kanan Seorang Remaja

Abstract: Background: Foreign bodies can come from outside the body (exogenous) and in the body (endogenous). Foreign bodies can cause total obstruction resulting in atelectasis or partial obstruction with emphysema. Case: A 14-year-old girl with a cough with phlegm mixed with blood spots one day before admission. Patients swallowed needle 10 days ago while wearing jilbab while joking at school. Chest X-rays appear density of a metal with a long straight form of about 3.5 cm projected in the lower right hemitorac. Discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Rigid bronchoscopy with magnifying telescope produces superior visualization and adequate ventilation, which is recommended in managing FBA, including those with complications such as hemoptysis, surrounded by granulation tissues, or sharp FBs requiring certain manoeuvres [11,15]. The success rate of rigid bronchoscopy reached 90.4% in the first attempt in Egypt [11,17]. Ganie et al reported 52/55 patients with successful extraction, whilst 3/55 patients underwent thoracotomy [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigid bronchoscopy with magnifying telescope produces superior visualization and adequate ventilation, which is recommended in managing FBA, including those with complications such as hemoptysis, surrounded by granulation tissues, or sharp FBs requiring certain manoeuvres [11,15]. The success rate of rigid bronchoscopy reached 90.4% in the first attempt in Egypt [11,17]. Ganie et al reported 52/55 patients with successful extraction, whilst 3/55 patients underwent thoracotomy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Flexible bronchoscopy is relatively more accessible and safer under an experienced operator. The mortality rate declined from 12% to 1% with flexible bronchoscopy compared with rigid bronchoscopy [15,17]. A systematic review showed a successful extraction rate of 61-100% with flexible bronchoscopy compared with 3-40% with rigid bronchoscopy [3,19].…”
Section: Discussionmentioning
confidence: 99%